Mekanisme Pembentukan Struktur Geologi Daerah Batu Ampar Dan Sekitarnya, Kabupaten Bengkulu Selatan, Provinsi Bengkulu - Zaki Nurul Zaid; Edy Sutriyono; Ugi Kurnia Gusti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study examines the mechanisms of geological structure formation in the Batu Ampar area and its surroundings through field geological mapping and interpretation of Digital Elevation Model (DEM) imagery data. Outcrop identification was conducted to determine the types of structures in tectonically deformed rocks. The observations reveal several geological structures, including the Air Kedurang I Anticline, Air Kedurang I Syncline, Air Kedurang II Anticline, Air Kedurang II Syncline, Air Kedurang III Anticline, and the Batu Ampar Thrust Fault. Structural element analysis was carried out using Win Tensor and Dips software. The analyzed data include plane orientations (strike and dip) and pitch for fault structures, while fold analysis utilized orientation data from both fold limbs. Stereonet analysis and DEM interpretation indicate that the structural orientations and surface relief patterns predominantly trend northwest–southeast (NW–SE). The results suggest that compressional forces during the Early to Late Pliocene led to fold formation, which continued into the Pleistocene and triggered the development of the Batu Ampar Thrust Fault. Overall, the geological structures in the study area are interpreted to have formed due to sustained NW–SE–oriented tectonic activity from the Pliocene to the Pleistocene.